2003
DOI: 10.1175/1520-0450(2003)042<0453:eochav>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of CALPUFF, HPAC, and VLSTRACK with Two Mesoscale Field Datasets

Abstract: Results of evaluations of transport and dispersion models with field data are summarized. The California Puff (CALPUFF), Hazard Prediction and Assessment Capability (HPAC), and Chemical/Biological Agent Vapor, Liquid, and Solid Tracking (VLSTRACK) models were compared using two recent mesoscale field datasetsthe Dipole Pride 26 (DP26) and the Overland Along-wind Dispersion (OLAD). Both field experiments involved instantaneous releases of sulfur hexafluoride tracer gas in a mesoscale region with desert basins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 6 publications
3
46
0
Order By: Relevance
“…These typically include, the normalized mean square error (NMSE), the fraction of predictions within a factor of 2 of the observations (FAC2), the fractional bias (FB), the geometric mean bias (MG) and the geometric variance (VG) (see Appendix A for definitions). In the absence of any universally agreed performance criteria, when authors wish to compare their results to those of others, they generally cite the criteria for an 'acceptable model' proposed by Chang and Hanna (e.g., [16][17][18][19][20][21][22]), which are summarized in Table 2. The Chang and Hanna criteria were based on their experience in conducting a large number of model evaluation exercises [23].…”
Section: Performance Metricssupporting
confidence: 88%
“…These typically include, the normalized mean square error (NMSE), the fraction of predictions within a factor of 2 of the observations (FAC2), the fractional bias (FB), the geometric mean bias (MG) and the geometric variance (VG) (see Appendix A for definitions). In the absence of any universally agreed performance criteria, when authors wish to compare their results to those of others, they generally cite the criteria for an 'acceptable model' proposed by Chang and Hanna (e.g., [16][17][18][19][20][21][22]), which are summarized in Table 2. The Chang and Hanna criteria were based on their experience in conducting a large number of model evaluation exercises [23].…”
Section: Performance Metricssupporting
confidence: 88%
“…The FA2 values for LH range from 57-71% depending on the stability, which is very high compared with results from Terada et al (2004) who reported only 33% for the new version of WSPEEDI (a regional model simulation). Our models also compare well against the three models evaluated by Chang and Franzese (2003), who found FA2 results of 52%, 60% and 43% for CALPUFF, HPAC and VLSTRACK models respectively. However, both of these studies were conducted on much larger scales, so the current results are unsurprising.…”
Section: Comparison Of Results With Recent Studiesmentioning
confidence: 99%
“…Recent dispersion model evaluations using nonradiological species include the study of Chang and Franzese (2003) which compares the California Puff (CALPUFF) model, the Hazard Prediction and Assessment Capability (HPAC) and the Chemical/Biological Agent Vapor, Liquid, and Solid Tracking (VLSTRACK) model using data from a recent mesoscale field campaign (Dipole Pride 26, DP26) in which 30 air samplers measured 15 min-average concentrations of SF 6 over a three-hour period. However, only hourly averaged concentrations were used in their results, since CALPUFF cannot produce higher frequency data.…”
Section: Model Evaluation Techniques and Recent Studiesmentioning
confidence: 99%
“…To assess whether the conclusions regarding the effect of the NEXRAD wind retrievals on the overall dispersion presented in Section 5.3 were specific to CALPUFF, we also performed a series of simulations using the Second-order Closure Integrated PUFF (SCIPUFF) model (Sykes et al 1993(Sykes et al , 2004). The SCIPUFF model performs the dispersion predictions as part of the Defense Threat Reduction Agency's (DTRA's) Hazard Prediction and Assessment Capability (HPAC) used by the U.S. Department of Defense (DTRA 2001;Warner et al 2004;Chang et al 2003Chang et al , 2005. CALMET and SCIPUFF are also being used to represent dispersion for the Biological Warning and Incident Characterization (BWIC) system currently being developed by DHS.…”
Section: Comparison Of Calpuff and Scipuffmentioning
confidence: 99%